Breakage of CRISPR/Cas9-Induced Chromosome Bridges in Mitotic Cells - Rodriguez-Muñoz, Marina; Serrat, Martina; Soler, David; Genescà, Anna; Anglada, Teresa (Frontiers in Cell and Developmental Biology, 2021)
Chromosomal instability, the most frequent form of plasticity in cancer cells, often proceeds through the formation of chromosome bridges. Despite the importance of these bridges in tumor initiation and progression, debate remains over how and when they are resolved. In this study, we investigated the behavior and properties of chromosome bridges to gain insight into the potential mechanisms underlying bridge-induced genome instability. We report that bridges may break during mitosis or may remain unbroken until the next interphase. During mitosis, we frequently observed discontinuities in the bridging chromatin, and our results strongly suggest that a substantial fraction of chromosome bridges are broken during this stage of the cell cycle. This notion is supported by the observation that the chromatin flanking mitotic bridge discontinuities is often decorated with the phosphorylated form of the histone H2AX, a marker of DNA breaks, and by MDC1, an early mediator of the cell response to DNA breaks. Also, free 3'OH DNA ends were detected in more than half of the bridges during the final stages of cell division. However, even if detected, the DNA ends of broken bridges are not repaired in mitosis. To investigate whether mitotic bridge breakage depends on mechanical stress, we used experimental models in which chromosome bridges with defined geometry are formed. Although there was no association between spindle pole separation or the distance among non-bridge kinetochores and bridge breakage, we found a direct correlation between the distance between bridge kinetochores and bridge breakage. Altogether, we conclude that the discontinuities observed in bridges during mitosis frequently reflect a real breakage of the chromatin and that the mechanisms responsible for chromosome bridge breakage during mitosis may depend on the separation between the bridge kinetochores. Considering that previous studies identified mechanical stress or biochemical digestion as possible causes of bridge breakage in interphase cells, a multifactorial model emerges for the breakage of chromosome bridges that, according to our results, can occur at different stages of the cell cycle and can obey different mechanisms.